Fabrication of a Thermosensitive In Situ Gel Nanoemulsion for Nose to Brain Delivery of Temozolomide. (13th March 2021) - Bayanati, Masoumeh; Khosroshahi, Abolfazl Ghafouri; Alvandi, Maryam; Mahboobian, Mohammad Mehdi
Abstract : In this study, a thermosensitive in situ gel nanoemulsion was formulated by a low energy method for intranasal delivery of temozolomide to bypass the blood-brain barrier and optimize chemotherapy for glioblastoma. Various amounts of Labrasol, Transcutol®P, and Triacetin were chosen as nanoemulsion components based on the solubility and the partial pseudoternary phase diagrams studies. Poloxamer derivatives added to the selected nanoemulsion and gelling temperature optimized. The prepared in situ gel nanoemulsion containing temozolomide showed a mean droplet size of 16.25 ± 0.44   nm, a polydispersity index value of 0.35 ± 0.01, and desirable pH and viscosity. In vitro release studies revealed that both nanoemulsion and in situ gel preparation have sustained release pattern in comparison to the control solution. Visual evaluation and droplet size and polydispersity index measurements showed both nanoemulsion and in situ gel nanoemulsion were stable during heating-cooling and freeze-thaw cycles and also centrifugation. Mucoadhesion percentage of in situ gel nanoemulsion was 37.037 ± 2.32 regarding ex vivo studies, which had a significant rise in comparison to control solution and nanoemulsion. Permeation across the nasal mucosa was 1.43- and 1.52-fold higher than the control solution for nanoemulsion and in situ nanoemulsion, respectively. Gamma scintigraphy study showed brain accumulation of developed nanoemulsion formulations. Our studies demonstrated optimized formulation has suitable physicochemical properties, desirable release profile, enhanced permeation across the nasal mucosa, and prolonged resistance time at the nasal mucosa. Therefore, in situ gel nanoemulsion would be an effective novel nasal delivery system for the treatment of glioblastoma.